Preditores sociodemográficos relacionados com feridas crônicas e conhecimento popular sobre seu tratamento - Capello, Ellen Maria Candido de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Introdução: As úlceras ou feridas crônicas, são lesões de pele que não cicatrizam e que podem comprometer desde a epiderme até as camadas mais profundas, como músculos, tendões e ossos. Definir um tratamento ideal, ainda é um desafio. A cicatrização, envolve a adesão ao tratamento pelo paciente, a reação do organismo à proposta terapêutica, o comportamento do paciente em relação aos cuidados com a ferida, o manejo com o curativo e os aspectos gerais da manutenção de sua saúde. As demandas sociais, econômicas e culturais, geram fortes influências no tratamento das feridas e atrapalham indiretamente a cicatrização. Objetivos: Correlacionar fatores sócio demográficos e educacionais como preditores para a ocorrência de feridas crônicas, comparando-se indivíduos saudáveis com portadores de feridas crônicas. Casuística e Método: Foram utilizados dois questionários semiestruturados, distintos e customizados com dados sócio demográficos e aspectos da doença. Delimitou-se duas populações: Grupo 1 - constituído pela população geral saudável e o Grupo 2 - constituído por pessoas portadoras de feridas crônicas. Resultados e discussão: Os dois grupos conhecem algum tipo de tratamento caseiro para tratar feridas, contudo não detém conhecimento suficiente sobre feridas crônicas e das terapias convencionais prescritas pela medicina. Ambos os grupos possuem crenças, mitos e preconceitos sobre cicatrização de feridas. Paciente e família não recebem informações por escrito de como devem fazer o curativo de suas feridas. Essas informações direcionaram a confecção de um manual de feridas e curativos com linguagem simples a toda população. Conclusão: A adoção de terapias não convencionais para o tratamento de feridas crônicas é frequente pela população. A falta de conhecimento, comportamentos equivocados, trazem prejuízos para a cicatrização das feridas. Faz-se necessário a produção e oferta de fontes informativas e educacionais com uma linguagem adequada e acessível, favorecendo o conhecimento sobre a prevenção, o tratamento adequado, a cicatrização das feridas e a qualidade de vida.

Chronic wound is still a challenge for medicine, either to define its cause and for selecting an optimal treatment. Healing is a long and complex process. It involves adherence to the treatment by the patient, the reaction of the organism to the therapeutic treatment, the patient's behavior regarding wound care, handling the dressing, and general aspects to maintain health, especially if there are other chronic diseases. Social, economic and cultural demands can also generate strong influences upon the treatment of wounds and healing process, since the population, in general, believes in myths, misconceptions and prejudices about wound healing, a knowledge that has been passed on empirically for generations, which may be harmless or extremely harmful. The objective of this study was to correlate socio-demographic and educational factors as predictors for the occurrence of chronic wounds, comparing healthy individuals with patients with chronic wounds. Two semistructured instruments were employed; a questionnaire, specific and customized, seeking socio demographic data, knowledge about chronic wounds, medical treatment of wounds, alternative and unconventional therapies and knowledge about bio-curative. Two populations were delimited: Group 1 - constituted by the healthy population, in general, and Group 2 - constituted by people with chronic wounds. It was observed that both groups are aware of some kind of home treatment to treat wounds, but they do not have sufficient knowledge about chronic wounds and conventional therapies prescribed by medicine. Regardless of the socioeconomic or educational level, both groups have outdated beliefs, myths and prejudices about wound healing. Even under medical treatment, the patient and the family generally do not have specific, directed and written information concerning care and wounds dressings, impairing the effectiveness of the therapeutic process. Health teams should offer holistic assessment and try to demystify beliefs, myths and prejudices of patients, avoiding complications in the healing process. It can be concluded that the adoption of non-conventional therapies for the treatment of chronic wounds is still very frequent in the population affected by this disease. Lack of knowledge about the treatment of chronic wounds can lead patients and families to incorrect procedures, impairing the wound healing. Realizing the importance of a correct treatment concerning chronic wounds and dressings to the population and especially patients, a manual of chronic wounds and dressings was developed, using a non-technical approach, in a suitable and accessible language, specially directed to the population, in general, and patients with chronic wounds, in order to inform about prevention, treatment and improvement of the quality of life of the populations, which are directly or indirectly affected by this disease. Keywords: Popular Knowledge; Wounds and lesions; Manuals; Wound healing techniques; Treatment of chronic wounds.
Sociodemographic predictors related to chronic wounds and popular knowledge about the treatment
Keywords: Conhecimento popular; Ferimentos e lesões; Manuais; Técnicas de fechamento de feridas; Tratamento de feridas crônicas; Popular Knowledge; Wounds and lesions; Manuals; Wound healing techniques; Treatment of chronic wounds